Proactive Personality and Creative Performance: Mediating Roles of Creative Self-Efficacy and Moderated Mediation Role of Psychological Safety - Suk Bong Choi (MDPI AG, 2021)
Previous research has suggested that employees’ proactive personality can enhance their creative performance. However, studies that address the underlying mechanism of the effect of proactive personality on creative performance have been scarce. Additionally, contextual factors that could serve as useful conditions have received insufficient academic attention. Therefore, the present study proposed that creative self-efficacy serves as a mediator and psychological safety serves as a moderator in the positive relationship between employees’ proactive personality and their creative performance. The results of a large-scale survey revealed that a proactive personality was positively associated with creative performance. Furthermore, we found that the positive relationship between a proactive personality and creative performance was positively mediated by creative self-efficacy and further strengthened by psychological safety. Additionally, we found that psychological safety influenced the mediating role of creative self-efficacy in the link between employees’ proactive personality and creative performance. We have discussed theoretical and practical implications with future research directions.